Legal and Criminological Analysis of the Crime of Abortion from the Perspective of Criminal Law in Indonesia - Johan Alfred Sarades Silalahi; Novelina Mutiara S Hutapea; Jenriswandi Damanik; Senni Pionita Saragih; Desy Kartika C. Sitepu (Academic Solution Publisher, 2025)
Abortion or termination of pregnancy is a controversial issue that causes debate between the pros and cons in society, where abortion cases continue to increase every year and can occur in various circles, including teenagers who are involved in free sex, but in positive law in Indonesia, abortion in certain cases can be justified if it is an abortion provokatus medicinalis, while abortion that is generalized as a criminal act is known as abortion provokatus criminalis, so in this study three main problems were studied, namely the factors that encourage a woman to commit the crime of abortion, the application of criminal sanctions for the crime of abortion, and efforts to overcome it, using library research methods, and from the results of the analysis it was found that socio-economic factors such as financial inability, pregnancy due to rape, and pregnancy outside of marriage are the main drivers for women to have illegal abortions as a solution to unwanted pregnancies; the application of criminal sanctions against perpetrators of abortion can only be carried out if there is an element of error in the act which violates the provisions as regulated in Article 77A paragraph (1) of Law Number 35 of 2014 concerning amendments to Law Number 23 of 2002 concerning Child Protection, which states that anyone who intentionally carries out an abortion on a child who is still in the womb for reasons and procedures which are not permitted by statutory regulations as referred to in Article 45A, can be subject to a maximum prison sentence of ten years and a maximum fine of one billion rupiah; and efforts to overcome abortion can be carried out through pre-emptive, preventive, and repressive strategies, where pre-emptive efforts are carried out through routine counseling on abortion, socialization of reproductive health, and appeals to parents and the community to carry out strict supervision and provide positive activities to build the future of the younger generation, while preventive efforts are carried out through cooperation between law enforcement and health institutions such as the Doctors Association, Police Medicine, Forensic Laboratory, and the Ministry of Health to provide guidance to women who experience unwanted pregnancies so that they do not have illegal abortions, while repressive efforts are carried out through law enforcement by imposing penalties on perpetrators in accordance with applicable provisions